COVID-19 coagulopathy and thrombosis: Analysis of hospital protocols in response to the rapidly evolving pandemic. Issue 196 (December 2020) - Parks, Anna L.; Auerbach, Andrew D.; Schnipper, Jeffrey L.; Anstey, James E.; Sterken, David G.; Hecht, Todd E.H.; Fang, Margaret C.; ,; Vaughn, Valerie M.; Dunn, Andrew S.; Linker, Anne S.; Hunt, Daniel P.; et al.
Abstract: As the Coronavirus disease 2019 (COVID-19) pandemic spread to the US, so too did descriptions of an associated coagulopathy and thrombotic complications. Hospitals created institutional protocols for inpatient management of COVID-19 coagulopathy and thrombosis in response to this developing data. We collected and analyzed protocols from 21 US academic medical centers developed between January and May 2020. We found greatest consensus on recommendations for heparin-based pharmacologic venous thromboembolism (VTE) prophylaxis in COVID-19 patients without contraindications. Protocols differed regarding incorporation of D-dimer tests, dosing of VTE prophylaxis, indications for post-discharge pharmacologic VTE prophylaxis, how to evaluate for VTE, and the use of empiric therapeutic anticoagulation. These findings support ongoing efforts to establish international, evidence-based guidelines. Highlights: COVID-19 protocols agreed on heparin-based venous thromboembolism prophylaxis. Disagreement on thrombosis risk and diagnosis, D-dimer, empiric anticoagulation Cumulative incidence of COVID-19 did not correlate with specific recommendations. Framework for frontline providers and hospitals to evaluate practices and outcomes